Occupational Exposure to Formaldehyde and Cancer Risk Assessment in an Anatomy Laboratory - Dragan Adamović (MDPI AG, 2021)
Dissecting a human cadaver is an irreplaceable practice in general training of medical students. Cadavers in anatomy laboratories are usually preserved in formalin, an embalming fluid whose basic component is formaldehyde (FA). The aim of this study is to assess the cancer risk of employees and students that are exposed to FA based on the results of three monitoring campaigns, as well as to suggest permanent solutions to the problem of FA exposure based on the results obtained. Three sampling campaigns of formaldehyde concentration in indoor environments were conducted at five different locations at the Anatomy Department of the Faculty of Medicine with the purpose of assessing permanent employees’ and medical faculty first year students’ exposure to FA. Indoor air was continuously sampled during 8 h of laboratory work and analyzed in accordance with the NIOSH Method 3500. Exceeding of the 8 h time-weighted average (8 h TWA) values recommended by Occupational Safety and Health Administration (OSHA) of 0.75 ppm was recorded in 37% of the samples during the three-month monitoring campaign. Cancer risk assessment levels for permanent employees were in the range from 6.43 × 10−3 to 8.77 × 10−4, while the cancer risk assessment levels for students ranged from 8.94 × 10−7 to 1.83 × 10−6. The results of the research show that cancer risk assessment for employees is several thousand times higher than the limit recommended by the EPA (10−6) and point to the importance of reducing exposure to formaldehyde through the reconstruction of the existing ventilation system, continual monitoring, the use of formaldehyde-free products, and plastination of anatomical specimens.